2021
DOI: 10.1016/j.celrep.2021.109874
|View full text |Cite
|
Sign up to set email alerts
|

p38-mediated cell growth and survival drive rapid embryonic wound repair

Abstract: Highlights d p38 MAPK is activated in cells adjacent to wounds in Drosophila embryos d Defective p38 signaling delays wound closure without affecting myosin II dynamics d p38 activation promotes an increase in cell volume that drives rapid wound repair d p38 limits wound size by reducing ROS levels in the cells adjacent to the wound

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 103 publications
(136 reference statements)
0
13
0
Order By: Relevance
“…Recent data revealed that these cells might be doing more than simply stretching: cells adjacent to epidermal wounds in axolotl, zebrafish, and Drosophila embryos increase their volume in a process necessary for rapid wound healing ( Tanner et al. , 2009 ; Kennard and Theriot, 2020 ; Scepanovic et al. , 2021 ).…”
Section: Do the Materials Properties Of Tissues Affect Aj Remodeling ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent data revealed that these cells might be doing more than simply stretching: cells adjacent to epidermal wounds in axolotl, zebrafish, and Drosophila embryos increase their volume in a process necessary for rapid wound healing ( Tanner et al. , 2009 ; Kennard and Theriot, 2020 ; Scepanovic et al. , 2021 ).…”
Section: Do the Materials Properties Of Tissues Affect Aj Remodeling ...mentioning
confidence: 99%
“…, 2011 ; Xu and Chisholm, 2011 ; Holt et al. , 2021 ; Scepanovic et al. , 2021 ), the development of activity sensors to track the dynamics of channel activation during wound repair ( Stewart et al.…”
Section: Do the Materials Properties Of Tissues Affect Aj Remodeling ...mentioning
confidence: 99%
“…Axolotl skin explants heal slower in the presence of hypertonic media (Tanner et al, 2009). With the opposite perturbation, hypotonic shock, zebrafish larvae and Drosophila embryos heal faster (Gault et al, 2014; Kennard & Theriot, 2020; Scepanovic, Hunter, Kafri, & Fernandez‐Gonzalez, 2021). Zebrafish, as a freshwater species, are thought to use such hypotonic shock as a normal signal for migration after wounding.…”
Section: Discussionmentioning
confidence: 99%
“…Axolotl skin explants heal slower in the presence of hypertonic media (Tanner et al, 2009). With the opposite perturbation, hypotonic shock, zebrafish larvae and Drosophila embryos heal faster (Gault et al, 2014; Kennard & Theriot, 2020; Scepanovic et al, 2021). Zebrafish, as a freshwater species, are thought to use such hypotonic shock as a normal signal for migration after wounding.…”
Section: Discussionmentioning
confidence: 99%